The implementation of a hospital's fall management protocol: results of a four-year follow-up - Correa, Arlete Duarte; Marques, Ifigênia Augusta Braga; Martinez, Maria Carmen; Laurino, Patrícia Santesso; Leão, Eliseth Ribeiro; Chimentão, Denise Maria Nascimento (Revista da Escola de Enfermagem da USP, 2012)
Inpatient falls are common occurrences with negative effects for patients and institutions. The objective of this descriptive study was to present the results of a fall management protocol used in a private hospital located in São Paulo, Brazil. Follow-up consisted of reviewing the fall rates and performing a descriptive analysis of the data. Subjects were the patients admitted between 2005 and 2008, accounting for 284 falls in 207,067 patient-days. The rates showed a monthly variability, with reductions following the implementation of interventions and rises in rates after management actions and training. In 2008, falls were more frequent among patients in clinical units of greater complexity - the elderly - using drugs that affected the central nervous system or having an impaired gait. The performed actions caused a reduction in fall rates, and the characterization of the events permitted staff to redirect interventions focusing on patients who were more susceptible to falls, as well as strengthen educational actions.